2007
DOI: 10.4049/jimmunol.179.12.8090
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Inducible NO Synthase Activity In Vivo Reverses Inflammatory Abnormalities in Surfactant Protein D-Deficient Mice

Abstract: Surfactant protein D (SP-D)-deficient (SP-D−/−) mice exhibit early development of emphysema. Previously we have shown that SP-D deficiency results in increased production and activity of inducible NO synthase (iNOS). In this study, we examined whether treatment with the iNOS inhibitor 1400W could inhibit the inflammatory phenotype. Mice were treated with 1400W systemically for 7 wk from 3 wk of age. Treatment reduced total lung NO synthase activity to 14.7 ± 6.1% of saline-treated 10-wk-old SP-D−/− littermates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…These findings provide evidence that iNOS-dependent protein nitration in alveolar type 2 cells accompanies but is not necessary for the development of elastase-induced pulmonary emphysema in mice. Increases in lung iNOS expression and protein nitration were previously described in the lungs of patients with COPD 7 as well as in experimental emphysema induced by inhibition of the VEGF receptor or surfactant protein D deficiency 18,19 ; whether these phenomena contributed to airspace enlargement in these models was not reported, but could be suspected as iNOS contributes to inflammation and tissue remodeling in other models of lung injury such as endotoxin-induced pneumonitis, 17 ventilator-induced lung injury, 16 and silica-induced pulmonary fibrosis. 20 In contrast with these observations, we observed that, whereas iNOS was strongly induced in the lung following elastase instillation, iNOS inhibition had no evident impact on pulmonary inflammation or emphysema development in this model.…”
Section: Discussionmentioning
confidence: 77%
“…These findings provide evidence that iNOS-dependent protein nitration in alveolar type 2 cells accompanies but is not necessary for the development of elastase-induced pulmonary emphysema in mice. Increases in lung iNOS expression and protein nitration were previously described in the lungs of patients with COPD 7 as well as in experimental emphysema induced by inhibition of the VEGF receptor or surfactant protein D deficiency 18,19 ; whether these phenomena contributed to airspace enlargement in these models was not reported, but could be suspected as iNOS contributes to inflammation and tissue remodeling in other models of lung injury such as endotoxin-induced pneumonitis, 17 ventilator-induced lung injury, 16 and silica-induced pulmonary fibrosis. 20 In contrast with these observations, we observed that, whereas iNOS was strongly induced in the lung following elastase instillation, iNOS inhibition had no evident impact on pulmonary inflammation or emphysema development in this model.…”
Section: Discussionmentioning
confidence: 77%
“…Surfactant protein D deficient mice also exhibit an increase in inflammatory mediators in the lung including metalloproteinases, IFN-␥ and reactive oxygen species accompanied by early emphysematous changes in the lung (34,35). Selective inhibition of iNOS activity in vivo reverses inflammatory abnormalities in Surfactant protein D deficient mice (36). Alveolar macrophage PPAR␥ expression has not been investigated in this animal model.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier work reported on increased constitutive expression of iNOS in macrophages and alterations in nitric oxide metabolites in the lungs of Sftpd 2/2 mice (17). Moreover, treatment of these mice with an iNOS inhibitor attenuated the inflammatory responses associated with a loss of Sftpd (37). The favoring of proinflammatory macrophage activation in the lungs of Sftpd 2/2 mice, which occurs as a consequence of excessive iNOS activity, may lead to a hypersusceptible state, such that ozone-mediated injury and oxidative stress are prolonged.…”
Section: Discussionmentioning
confidence: 99%